Cancer‐related fatigue in teenage and young adult cancer patients: Clinicians' perspectives, practice and challenges. (4th October 2020) - Willmott, Emma; Loades, Maria; Baker, Laura; Spathis, Anna
Abstract: Objective: Cancer‐related fatigue (CRF) is a common and distressing symptom experienced by teenage and young adult cancer patients (TYAs). This study aimed to explore clinicians' perspectives, practices and challenges in supporting TYAs with CRF. Method: Ten clinicians from a TYA multidisciplinary team (MDT) participated in semi‐structured interviews which were thematically analysed. Results: Clinicians perceived CRF as a common, but individual experience for TYAs and framed the broad impact of CRF in the context of TYAs' development. Clinicians' assessment and management of CRF for TYAs varied. Clinicians described a range of challenges affecting their practice in supporting TYAs with CRF, including limited knowledge, difficulties engaging TYAs, inadequate time in consultations and a lack of age‐appropriate resources. Conclusions: Despite clinicians' good insight into TYAs' unique experiences of CRF, the assessment and management of CRF for TYAs are complicated by numerous challenges. The development of evidence‐based interventions and guidelines, clear pathways of care, and TYA‐friendly resources, measures and programmes, is vital to support clinicians, and TYAs, in managing CRF.